2003
DOI: 10.1152/ajpcell.00043.2003
|View full text |Cite
|
Sign up to set email alerts
|

Atypical protein kinase C mediates activation of NF-E2-related factor 2 in response to oxidative stress

Abstract: Transcription factor NF-E2-related factor 2 (Nrf2) regulates the induction of antioxidative proteins, including heme oxygenase-1 (HO-1). Nrf2 is sequestered in the cytoplasm by Keap1 under unstimulated conditions but translocates into the nucleus and transactivates the antioxidant responsive element (ARE) upon exposure to oxidative insults. It has recently been demonstrated that in vitro phosphorylation of Nrf2 on Ser40 by protein kinase C (PKC) facilitates the dissociation of Nrf2 from the Keap1 complex (Huan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(202 citation statements)
references
References 62 publications
8
192
1
1
Order By: Relevance
“…In contrast to PKC-β, the novel PKC-δ activity was inhibited by 0.1 μM HNE but increased by 1-10 μM HNE (199,200) . Numazawa also reported that HNE-mediated HO-1 induction was completely abrogated by dominant-negative expression of atypical PKC-ι (201), suggesting that HNE may also activate PKC-ι.…”
Section: A Activation Of Protein Kinase C By Hnementioning
confidence: 93%
“…In contrast to PKC-β, the novel PKC-δ activity was inhibited by 0.1 μM HNE but increased by 1-10 μM HNE (199,200) . Numazawa also reported that HNE-mediated HO-1 induction was completely abrogated by dominant-negative expression of atypical PKC-ι (201), suggesting that HNE may also activate PKC-ι.…”
Section: A Activation Of Protein Kinase C By Hnementioning
confidence: 93%
“…74 Various isoforms of PKC and atypical PKC have been documented to be involved in phosphorylation of Nrf2. 15,75 Phosphatidylinositol 3-kinaseemediated phosphorylation of Nrf2 and its dissociation, nuclear translocation, and subsequent induction of antioxidants have been shown in human neuroblastoma cells. 76 In addition to the involvement of PKC and phosphatidylinositol 3-kinase in the activation of Nrf2, accumulating evidence suggests a role for mitogenactivated protein kinases 19,77,78 ; however, some reports suggest negative regulation of Nrf2 by these protein kinase pathways.…”
Section: Keap1-independent Mechanismsmentioning
confidence: 99%
“…It has been shown that Daxx interacts with HSF1 (the nuclear concentration of which is increased following HNE exposure) and upregulates the expression of HSF1-associated genes. Likewise, it is known that interaction of Daxx with other transcription factors such as ETS1, Pax 3, Pax5, smad4, and p53 also affects the expression of the associated genes [104][105][106][107]. Thus, HNE can influence a large set of fundamental cellular processes including proliferation, cell cycle events, and apoptosis and can modulate the expression of numerous genes.…”
Section: Hne and Transcription Repressors/factorsmentioning
confidence: 99%